Urine Clean Catch Collection in the Paediatric Emergency Department: Success, Time to Void and Contamination Rates. (1st June 2016) - Kaufman, J; Tosif, S; Fitzpatrick, P; Donath, S; Hopper, S; Bryant, P; Babl, F
Abstract: BACKGROUND: Young children frequently require investigation for urinary tract infection (UTI). Clean catch urine (CCU) is a common urine collection method in pre-continent children but can be time consuming or unsuccessful, and contaminated cultures may lead to an inability to diagnose or exclude UTI. There are few data available examining the success and time required for CCU and factors influencing contamination. We hypothesise that time taken to obtain CCU influences contamination, due to accidental contamination during collection. OBJECTIVES: To determine the time taken to obtain CCU in pre-conti-nent children, and if time to collection is related to the contamination rate. DESIGN/METHODS: Prospective observational study of CCU collection in pre-continent children aged 2-48 months at a paediatric emergency department in Australia. A standardised CCU collection protocol was used. Primary outcome was time to first void; secondary outcomes were success of obtaining (catching) CCU and contamination of urine cultures obtained. Contamination was defined as per hospital microbiology standards. Descriptive analysis of time to void included median and interquartile range (IQR). We performed a regression analysis of key factors possibly related to contamination, including age, sex and time to collection. RESULTS: Of the 218 recruited patients, 61% were male, mean age 11.4 months (SD 8.5). The main indication for CCU was: 128 fever of unknown origin (59%), 31 vomiting (14%), 27 specifically suspected UTI (12%), 32 other reason (15%). From first CCU attempt, 174 voided (80%) of which 139 were successful catches (64%) and 34 were missed on voiding (16%). 44 first CCU attempts were stopped before voiding (20%), 26 patients had 2 attempts (12%), and 2 patients had 3 CCU attempts (1%). Median time to first void was 25 minutes (IQR 8 – 49). 27 children (12%) voided <5 minutes, 33 (19%) voided >1hr. Of the 130 patients who had urine culture results available, 50 were contaminated (38%). There was no significant difference in contamination rate by age, sex or time to sample collection. Of 218 patients where ED clinicians set out to collect CCU in the emergency department, only 80 (37%) resulted in a successful CCU attempt with an uncontaminated culture. CONCLUSION: Contamination rates are high in clean catch urine, but not related to the time taken for sample collection. CCU attempts are often unsuccessful, and have a low diagnostic yield for investigation of UTI in young children in clinical practice.